Teaching Tourism Terminology as a Pedagogical Necessity in the Training of Guide-Interpreters - Akbarov Alisher Akhmadjonovich (Scientific Trends, 2025)
This article explores the pedagogical significance of teaching tourism terminology in the professional preparation of guide-interpreters. Given the rapid development of the global tourism industry and the increasing need for multilingual specialists, the role of English for Specific Purposes (ESP) and other modern methodological approaches is emphasized. The paper analyzes challenges in teaching tourism-specific vocabulary and provides practical solutions such as ESP, CLIL, and multimodal instruction. Based on current educational reforms in Uzbekistan, the study highlights the urgent need to align language instruction with the professional demands of the tourism sector.
Keywords: Tourism terminology, guide-interpreter, ESP, CLIL, multimodal learning, pedagogical necessity, Uzbekistan tourism.